Temelji gozdne ureditve revirja Unec 1908 - Perko, Franc (Gozdarski vestnik, 2008)
The article deals with the basic plan orientations of the Unec district in theyear 1908. Discovering the forests in question were not selection but uniform forests, the planner set a management system based on the clearcuttingprinciples. The plan shows the economical conditions at the beginning of the 20th century and the history of the forest management in the Haasberg estate.
Keywords: gozdno gospodarstvo; gozdnogospodarski načrti; prebiralni gozd; Unec; zgodovinski pregledi